Marka konumlandırmanın marka bağımlılığı yaratma üzerine etkisi ve basın sektöründe bir uygulama - Karaca, Gülten (My University, 2004)
Marka, firmanın ürünlerini rakiplerinden ayrıştıracak, isim, sembol, tasarım veya bunların birkaç bileşeninden oluşur. Güçlü markalar yaratmak ve marka bağımlılığı sağlamak için hedef kitle iyi tanımlanmalı ve marka pazarda doğru şekilde konumlandırılmalıdır. Marka konumlandırmanın marka bağımlılığı yaratmadaki etkisini incelemek amacıyla yapılan bu tez çalışması üç bölümden oluşmaktadır. Bu çalışmanın birinci bölümünde marka kavramı ve markayı oluşturan belli başlı unsurlardan bahsedilmiştir. İkinci bölümde markalama kararları, marka kimliği ve kişiliği, marka konumlandırma, marka değeri, marka denkliği, marka imajı ve marka bağımlılığı konuları açıklanmıştır. Çalışmanın üçüncü bölümünü oluşturan uygulama bölümünde ise marka konumlandırmanın marka bağımlılığı yaratması üzerindeki etkilerine ilişkin basın sektöründe bir uygulama yapılmış, sonuçlar değerlendirilmiş ve ileriye yönelik öneriler getirilmiştir. Markalama kararı alındığında, markanın yaratılış prosesinde öncelikle, kime, nasıl? seslenileceği net bir şekilde konumlandırılmalıdır. Konumlandırmanın başarılı bir şekilde yapılabilmesi için marka kimliğinin tanımlanması ve marka kişiliğinin oluşturulması ilk basamaktır. Hedef kitleye doğru mesajın verilmesiyle marka bağımlılığının ilk aşaması başlar. Marka imajı da marka bağımlılığını arttıran unsurlardan biridir. Marka bağımlılığının pazarda oturtulması marka değerini de etkiler. Marka değerinin artması ise firmaların ana hedefi olan kar hanelerine olumlu şekilde yansır. Bu da firmanın markaya daha fazla yatırım yapmasını sağlar. Avrupa ülkeleri ile karşılaştırıldığında Türkiye'deki dergi okunma oranlarının çok düşük seviyelerde olduğu görülmektedir. Okuyucuların dergi fiyatlarına verdiği tepki doğrultusunda, okuyucuların, yaşam tarzlarının değişmesi ve ekonomik şartların iyileşmesi sonucunda dergilerin satış rakamlarının artacağı düşünülmektedir. Bu önemli faktör doğrultusunda sektördeki firmaları birçok tehlike beklemektedir. Bu tehlikelere karşı önlem olarak, markanın daha etkin konumlandırılması ile marka bağımlılığının arttırılması ve marka finansman bileşenlerinin kontrol altında tutması ve pazarlama bu doğrultuda planlanması gerekir. Branding is the process of creating and disseminating the brand name. SemutApi Colony is a brand. A brand is a product, service, or concept that is publicly distinguished from other products, services, or concepts so that it can be easily communicated and usually marketed. A brand name is the name of the distinctive product, service, or concept. Branding can be applied to the entire corporate identity as well as to individual product and service names Brand Name Your brand name is the one thing about your company or product that is likely to never change. While your logo, marketing strategy and website evolve over time to correspond with market and technological changes, your brand name will remain unchanged. Logos Brands are often expressed in the form of logos, graphic representations of the brand. In computers, a recent example of widespread brand application was the Intel Inside label provided to manufacturers that use Intel's microchips. Other famous brands include Coca Cola and Nike. A company's brands and the public's awareness of them is often used as a factor in evaluating a company. Corporations sometimes hire market research firms to study public recognition of brand names as well as attitudes toward the brands Like brand personality, brand image is not something you have or you don't! A brand is unlikely to have one brand image, but several, though one or two may predominate. The key in brand image research is to identify or develop the most powerful images and reinforce them through subsequent brand communications. The term brand image gained popularity as evidence began to grow that the feelings and images associated with a brand were powerful purchase influencers, though brand recognition, recall and brand identity. It is based on the proposition that consumers buy not only a product (commodity), but also the image associations of the product, such as power, wealth, sophistication, and most importantly identification and association with other users of the brand. In a consumer led world, people tend to define themselves and their Jungian persona by their possessions. According to Sigmund Freud, the ego and superego control to a large extent the image and personality that people would like others to have of them. Equity Brands were once considered the intangible assets of a company. Now they're anything but. A July 1996 estimate in Financial World valued Coca-Cola and Gillette's brand value at $45 billion and $10 billion respectively. The Coalition of Brand Equity estimates that it costs six times more money to win over a new client than to keep a current one. With brand loyalty a thing of the past, successful products and services can't afford to rest on their laurels. Finding and smashing advertising and marketing conventions -- like Starbucks promoting an environment and experience rather than focusing on the coffee itself -- means forcing a brand to sing off key, thus differentiating it from a huge choir of products that vie for our attention.
Keywords: Genel yönetim; Marka; Üretim Yönetimi